MEMBRANE CORRECTION FOR LATEX AND NEOPRENE/LATEX MEMBRANE AT TRIAXIAL COMPRESSION TEST (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
The influence of a rubber membrane is crucial in a triaxial compression test. Previous research has introduced methods such as compression shell theory and hoop tension theory to suggest a membrane correction for different types of specimen deformation during tests. Latex membranes often do not perform well if sharp particles are present due to membranes being punctured easily. Neoprene/Latex membranes perform better in triaxial compression tests as they are more resistant to punctures. In this research, a maximum error due to membrane performance was calculated for latex and Neoprene/Latex membranes using two analytical methods. The results indicate that errors for Neoprene/Latex membranes are greater than errors for latex membranes. Numerical modeling of Neoprene/Latex membranes shows that membrane diameter increases approximately linearly with corresponding lateral membrane pressure when specimens deform via buckling